Some Considerations on the Scientific Production of Agroturism from 1991 To 2023 - Lisbet Eunice Pérez Anzardo; Olga Lidia Ortiz Pérez; Reyner Pérez Campdesuñer (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2026)
The objective of this study was to describe the trends and current state of agritourism and the role of agritourism farms within it, based on a bibliometric study from its beginnings up to the year 2023. The source of information used was the Scopus Database. Theoretical methods such as analysis-synthesis and historical-logical approaches were employed, along with empirical methods including scientific observation, unstructured interviews, and the triangulation of sources and methods. Altogether, these allowed the identification of trends, regularities, and relationships in the phenomenon under study, based on the information obtained during the research process, as well as the formulation of conclusions. As a result, the foundations were established for further theoretical and practical exploration of the topic through the analysis of bibliometric indicators. From a population of 101 journals publishing on tourism management across various scientific fields, only 287 articles on agritourism were found, of which seven focused specifically on agritourism farms. In addition, a general overview of the subject was established, and the behavior of scientific production on agritourism from its origins to 2023 was described. Consequently, the insufficient analysis of agritourism farms as a distinctive element of this tourism modality and their contribution to territorial development was evidenced. The findings of this research provide a scientific basis to support strategic decision-making that links both the agricultural and tourism sectors in favor of territorial development.